Incorporating a continuous suction system as a preventive measure against fistula-related complications in head and neck reconstructive surgery - Hsien Pin Chang; Jong Won Hong; Won Jai Lee; Young Seok Kim; Yoon Woo Koh; Se-Heon Kim; Dae Hyun Lew; Tae Suk Roh (Archives of Plastic Surgery, 2018)
Background Although previous studies have focused on determining prognostic and causative variables associated with fistula-related complications after head and neck reconstructive surgery, only a few studies have addressed preventive measures. Noting that pooled saliva complicates wound healing and precipitates fistula-related complications, we devised a continuous suction system to remove saliva during early postoperative recovery.